Determination of Technological Risk Influences in a Port System Using Dematel - Sepulveda-Salas, J; Duran-San Martin, C; Carrasco-Armijo, R (Growing Science, 2018)
There is a little research about the relationship between risk and technology by using the DEMATEL model in a complex systems such as maritime port. Those studies neither include nor identify the relationships of technological risk generated between a Port Community and all the other actors who interact with it. This study presents the potential advantage of applying the DEMATEL to identify the synergic relationships at strategic and business levels produced by technological risk. The results determine the causes and the effects of decisions made by managers of port engineering community. They also affect the processes of information and communication logistics chains’ export and import. © 2018 Growing Science Ltd. All rights reserved.